2005
DOI: 10.1007/s11187-005-4259-7
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structure and Performance in Dutch small Firms

Abstract: ABSTRACT. The relationship between organizational structure and performance in small firms has received relatively limited attention over the last few decades. In understanding small firm performance this seems to be a serious omission. In this paper, we first present the rationale for including organizational structure in the analysis of small firm performance. Then, from the literature on organizational theory, we retrieve several dimensions that may be postulated to describe organizational structures of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 60 publications
(64 reference statements)
2
63
0
11
Order By: Relevance
“…Meijaard et al (73) have shown the direct relationship between organizational structure and firm performance in terms of sales growth, profitability and innovativeness. Since a series of different criteria should be considered in order to compare and choose an organizational structure (74) solely focusing on this factor cannot demonstrate any preferable organizational structure.…”
Section: Csfs For Corporation's Readinessmentioning
confidence: 99%
“…Meijaard et al (73) have shown the direct relationship between organizational structure and firm performance in terms of sales growth, profitability and innovativeness. Since a series of different criteria should be considered in order to compare and choose an organizational structure (74) solely focusing on this factor cannot demonstrate any preferable organizational structure.…”
Section: Csfs For Corporation's Readinessmentioning
confidence: 99%
“…Although there are various empirical studies (Russeeuw 1997;Wing and Yiu 1997;Meijaard et al 2005;Beise-Zee and Rammer 2006;Chiao et al 2006;Ooghe et al 2006;Rickne 2006;Sels et al 2006;Shin 2006;Andries and Debackere 2007) about the performance of SMEs, they do not analyse specifically the influence of size on performance, except for the studies by Russeeuw (1997) and Wing and Yiu (1997). However, the former does not take SMEs as its subject of study, only considering microcompanies.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to determination of responsibilities among employees and development of coordination mechanisms which are in fact the formation process of the firm structure. The organizational structure primarily focuses on two dimensions: the first dimension is the work division which is the distribution of work tasks and activities and the second dimension is the coordination mechanisms of the firm that is the level of standardization and formalization (Meijaard et al, 2005). The structure of an organization is important for the development and implementation of strategy, division of work and labor, coordination and integration of functions, and flow of information (Chrisman, 1999).…”
Section: Discussionmentioning
confidence: 99%